Estudo e implementação de interconectividade IPv6 entre roteadores LINUX e CISCO - Menine, Felipe Weiss (2014)
This Monograph describes in detail the behavior of a computer network interconnecting 2 routers from distinct vendors – a Cisco router and a Linux PC – in IPv6 using OSPFv3 protocol. On one hand, the well-known network equipment vendor and on the other, a router based on general-purpose PC using Open Source Operating System - Linux. The goal is to prove internetwork connectivity, bringing a low-cost alternative for an expanding network. Computer networks topics will be discussed with special attention to packet forwarding on Linux-installed HW. The outcome is a fully functional network, described in an in-depth tutorial for installation and configuration to serve as reference.